4′-hydroxywogonin inhibits colorectal cancer angiogenesis by disrupting PI3K/AKT signaling. (25th December 2018) - Sun, Dongdong; Zhang, Feng; Qian, Jie; Shen, Weixing; Fan, Huisen; Tan, Jiani; Li, Liu; Xu, Changliang; Yang, Ye; Cheng, Haibo
Abstract: Angiogenesis is fundamental for solid tumor growth and metastasis, and anti-angiogenic therapy has been an important therapeutic option for cancer treatment. Colorectal cancer (CRC) represents the fourth leading cause of cancer-related death worldwide. The current studies were aimed at investigating the anti-angiogenic effects of the natural compound 4′-hydroxywogonin (4′-HW) on CRC-related angiogenesis. Human CRC cell line SW620 cells and normal human intestinal epithelial HIEC cells were cultured and treated with interleukin-6 to mimic the tumor inflammatory microenvironment. Our data showed that 4′-HW reduced the viability of SW620 cells in a concentration- and time-dependent manner. 4′-HW also suppressed the proliferation of SW620 cells, but had little effect on the viability of HIEC cells. Moreover, 4′-HW concentration-dependently decreased the mRNA and protein expression of vascular endothelial growth factor-A (VEGF-A), the predominant pro-angiogenic cytokine in tumor angiogenesis. Subsequently, 4′-HW concentration-dependently inhibited the phosphorylation of phosphatidylinositol 3-kinase (PI3K) and AKT. PI3K inhibitor wortmannin, similar to 4′-HW, significantly downregulated the VEGF-A expression in SW620 cells, and combination of wortmannin and 4′-HW produced more significant effects. Finally, human umbilical vein endothelial cells (HUVECs) incubated with the conditioned medium of 4′-HW-treated SW620 cells exhibited impaired angiogenic capacity at Matrigel. Incubation with the neutralizing antibody against VEGF-Aalone also suppressed the angiogenic properties of HUVECs in vitro . Collectively, 4′-HW decreased the viability and reduced angiogenesis in CRC, which was associated with downregulation of VEGF-A expression by disrupting the PI3K/AKT pathway. Our discoveries suggested 4′-HW as a promising anticancer agent against CRC targeting angiogenesis. Graphical abstract: Highlights: 4′-HW reduced the viability of SW620 cells. 4′-HW decreased the mRNA and protein expression of VEGF-A. 4′-HW concentration-dependently inhibited the phosphorylation of PI3K and AKT.